Analysis of Underground Projects of Energy Efficient Low-Rise Residential Buildings Built on Highly Flooded Soils - Goyibov Oybek Inatillayevich; Matyokubov Bobur Pulatovich (Researchparks Publishing, 2021)
It is well known that energy saving in modern housing and housing sector remains an urgent problem. The main direction of comprehensive programs developed in this area is the development and application of energy-saving architectural solutions in buildings, as well as increasing the level of their thermal protection.Evidence suggests that doing this research is a requirement of the day, with the goal of developing constructive solutions for thermal insulation of basement walls and “increasing the energy efficiency of the basement of residential buildings”.